Estudio sobre el comportamiento visual en álgebra de los alumnos del segmento educativo 14-16 - Meavilla Seguí, Vicente (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1995)
The visual characterisation in Algebra of a sample of pupils in the 14-16 age -group has been studied. In this paper we suggest, in the light of the results of the study, didactic recommendations for the exploitation of visual reasoning in the teaching of Algebra in schools.